Pemberdayaan UMKM melalui Pendampingan Legalitas dan Strategi Pemasaran Digital di Kelurahan Mario Pulana - Marlinah, Andi; Bahasoan, Shandra; Asri, Asri; Khalik, Abdul; Usman, Irwan; Yassir, Muhammad (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
MSMEs in Mario Pulana Village, Maros Regency, face the challenge of low competitiveness due to limited business legality and visual identity. This community service aims to strengthen the capacity of 44 MSME actors by implementing four strategic pillars: product quality, technology, marketing, and human resource development. The method is a participatory approach that includes field observations, entrepreneurship seminars, and technical assistance with registering Business Identification Numbers (NIBs) through the Online Single Submission (OSS) system, as well as creating banner promotional materials. The results of the service show a significant shift from the informal to the formal sector, with the issuance of legal documents to partners. In addition, strengthening visual branding has increased professionalism and business visibility. The program significantly fosters new awareness of the importance of managerial aspects and legal compliance, while identifying local leaders as agents of change to ensure the sustainability of economic transformation at the village level.